Functional and Radiological Outcomes with Intramedullary Interlocking Nailing of Tibial Shaft Fracture - Kushwaha, Mukesh Prasad; Mourya, Vandana (Med Phoenix, 2022)
Introduction: Tibia is the most common long bone involved in fractureduring Road Traffic Accident (RTA) because of its subcutaneous location.Intramedullary nail fixation remains the treatment of choice for unstableand displaced tibial shaft fractures in the adult. The goals of surgicaltreatment are to achieve osseous union and to restore length, alignment,and rotation of the fractured tibia. Intramedullary nailing carries theadvantage of minimal surgical dissection with appropriate preservation ofblood supply to the fracture site.Materials and Methods: This is a prospective observational studyconducted in the Department of Orthopedics, National Medical College andTeaching Hospital,Birgunj, Parsa, Nepal for the 1 year duration. Patientsincluded in this study were above 16 years with Tibia shaft fracture with orwithout fibula fracture which includes Type I,II and IIIA of Gustilo-Andersonfracture. Patients with tibia shaft fracture were treated surgically by usingintramedullary interlocking nail then follow up done in OPD at regularintervals during which radiographs was taken in appropriate views anddiagnosis is established by functional and radiological means.Result: Out of 53 patients, 45 patients with Tibia shaft fracture are treatedby closed intramedullary interlocking nailing in the National MedicalCollege, Birgunj. Eight patients are lost during follow-up. In our studytibia shaft Fracture was more common in male (77.8%) than female whichmostly involved 18-30 years of age group (62.2%) and most common causewas Road Traffic Accident (82.2%). Thirty cases (66.7%) had excellent and10 cases (22.2%) had good healing and complication were seen in eightpatients (17.7%).Conclusion: Closed interlocking tibia nailing allows earlier fracture unionwith less morbidity. Because of the high union rate and low infection rate,we consider closed interlocking nailing as the best mode of treatment fordiaphyseal tibial fractures.